A case report of septic shock caused by opportunistic infections associated with anti-interferon-γ autoantibody positivity: diagnostic and therapeutic challenges - Shao, Jinlian; Xu, Xiao; Xie, Xunjie; Fan, Yiqi; Zhang, Dacheng; Tang, Waijiao (Frontiers in Medicine, 2025)
BackgroundSince 2004, there has been an increasing number of reports on severe, persistent, or recurrent Salmonella infections in adults with adult immunodeficiency associated with anti-gamma interferon antibody positivity (AIGA). AIGA patients experience rapid disease progression upon infection with opportunistic pathogens, high mortality rates, and strong disease latency, posing significant challenges for diagnosis and treatment. This article discusses the diagnosis and treatment strategies for AIGA with opportunistic pathogen infection through the diagnosis and treatment process of a 61-year-old male patient.MethodsThe patient presented with diarrhea and fever for 2 weeks and was diagnosed with non-typhoidal Salmonella infection at an external hospital. The condition progressed to shock and the patient was transferred to our EICU. After admission, the pathogens were confirmed through chest CT, blood culture, blood metagenomic next-generation sequencing (mNGS), and bronchoalveolar lavage fluid (BALF) mNGS, and cell immune function screening and anti-gamma interferon antibody testing were completed. The anti-infective treatment regimen was adjusted based on the test results, and immunoglobulin therapy was administered.ResultsThe patient’s blood culture was positive for non-typhoidal Salmonella, and blood mNGS confirmed non-typhoidal Salmonella and Legionella pneumophila; BALF mNGS showed Enterococcus faecium, Legionella pneumophila, Candida tropicalis, Candida glabrata, HSV1, and CMV mixed infection. Immune function screening indicated a significant decrease in CD4 + T cells (303 cells/μL) and a significant increase in anti-gamma interferon antibody (163.78 ng/mL), confirming the diagnosis of AIGA. After treatment with meropenem, linezolid, doxycycline, ganciclovir, and caspofungin combined with anti-infective and immunoglobulin therapy, the patient’s condition significantly improved and was discharged.ConclusionAIGA patients experience rapid disease progression after infection with opportunistic pathogens. Early identification of anti-gamma interferon antibody and mixed infection pathogens is crucial for treatment.